(untitled) (Nordic Journal of African Studies, 2003)
This article analyzes how administrative decentralization can improve the provision of social services in Africa. It uses political, economic, and historical approaches, to investigate the bureaucratic dysfunctions that administrative decentralization may reduce. It argues that administrative decentralization can overcome the all-time challenge for African central governments to broadcast authority over harsh and sparsely inhabited territories. Also, by tackling the use of public employment and wages to leverage distributive politics, it may reduce the distortions affecting the financing of public services, and which particularly undermine the quality of education. Administrative decentralization may also enhance merit-based appointments and promotions of bureaucrats by reducing the propensity to resort to public employment and wages as a means for political officials to reward loyalty and to recruit fellows. Finally, administrative decentralization may leverage effectively civil service reforms seeking to align central bureaucracies with the objective of poverty reduction through enhanced service delivery. Attention is drawn, however, to the conflicts that may arise, as administrative decentralization will come to threaten vested interests. The paper argues that for reformer international institutions, handling situations of political crises and learning how to use them to leverage reform will be critical for the success of administrative decentralization in Africa.